Introduction, production, characterization and applications of defects in graphene - Ahmad, Waqas; Ullah, Zaka; Sonil, Nazmina Imrose; Khan, Karim (Journal of materials science. Materials in electronics, 2021)
The successful preparation of graphene in research laboratory has brought a revolutionary progress in almost all the research fields including physical, chemical and biological sciences owing to its unique structural, electrical, chemical and optical properties. Being the first ‘two-dimensional (2D) material’, it has introduced a new class of ‘2D materials’. Continuous theoretical and experimental investigations are being made to know more about graphene to take more benefits from it. The structural properties of graphene are the fundamental properties which affect all its other properties. Defects in graphene can be considered a robust tool to tune its structural and other characteristics. In this review, we have summarized the recent and significant studies on defects in graphene. We have discussed different types of defects, how these can intentionally be produced, their influence on different properties of graphene and applications of defective graphene. This review presents a comprehensive study on all about defects in graphene and provides the basic understandings and worthy knowledge to researchers and scientists of this era for future studies to achieve the diversity of graphene applications.